Pharmacophore Based Virtual Screening and Docking of Different Aryl Sulfonamide Derivatives of 5HT7R Antagonist - Nahid Fatema; Vijjulatha Manga; Lingala Yamini; Salman Ahmad Khan; Qasim Ullah (Journal of Molecular Docking, 2022)
The selective blockade of 5HT7R (5-hydroxytryptamine 7 receptor) displays an antidepressant-like activity. It is a Gs-coupled receptor, which inactivates the adenyl cyclase enzyme or activates the potassium ion channel. Structural information of 5HT7 was obtained by homology modeling using MODELLER v.9.13. In the present study, pharmacophore-based virtual screening, molecular docking, and binding free energy calculations were performed on a series of antagonist aryl sulphonamide derivatives. A five-point pharmacophore hypothesis with two hydrogen bond acceptor (A), one hydrogen bond donor (D), one positive group (p), and one ring (R) was developed with acceptable R2 and Q2 values of 0.90 and 0.602, respectively. Eventually, common pharmacophore hypothesis-based screening was conducted against Asinex databases. Finally, binding free energy and dock score analysis was carried out for the top hits obtained from the docking process. All 14 hits from the database in this study had a satisfactory dock score and binding energy values within the best active compound range. H bond interaction with amino acid residues Ser212 and π-π stacking with Tyr249 were investigated for the best active molecule. Both are present in the top hits, including other interactions as well.